How William H. Kilpatrick’s Project Method Came to Germany: “Progressive Education” Against the Background of American-German Relations Before and After 1933 - Retter, Hein (International Dialogues on Education Journal, 2019)
This study shows which contacts and events were decisive for the publication of essays by John Dewey and William Kilpatrick as a German book in connection with Kilpatrick’s ensuing discussion after 1918 of the project method – in the middle of the Nazi era. The volume was edited in 1935, by Peter Petersen, at the University of Jena, the founder of the Jenaplan (Jena Plan). A number of previously unknown letters, information from various archives and Kilpatrick’s diaries, which are now available in digital form, were used. It was not possible to clarify all the details. However, it is certain that personal contacts and the educational exchange in American-German relations were not completely broken off with the beginning of Nazi rule in Germany in 1933.